MENINGKATNYA RISIKO CYBERBULLYING PADA ANAK-ANAK AKIBAT RELASI KELUARGA YANG KURANG BAIK DALAM PERSPEKTIF ANALISIS KOLOSE 3:18-21 - Muda, Stefanus Dama; Muda, Florianus Pruda (Bahasa Indonesia, 2024)
The family unit constitutes the smallest social structure, comprising of a father, mother, and their offspring. Within the family context, the cultivation of harmonious relationships between spouses and children is imperative. When these relationships falter, it can significantly impact the developmental trajectory and character formation of children. Consequently, children may exhibit undesirable behaviors within their family and the broader societal framework. One prevalent consequence is their susceptibility to cyberbullying, either as perpetrators or victims, resulting in various adverse effects on their academic, social, physical, and emotional well-being. These consequences are particularly pronounced in children who are vulnerable and lack the capacity to effectively address such issues. Therefore, there is a pressing need for an analysis aimed at addressing the escalating risk of cyberbullying among children stemming from suboptimal family relationships. This analysis adopts the perspective of Colossians 3:18-21, which addresses marital and familial relationships within the context of Christian life.